Using EM simulation to analyse the radiated emissions profile of an automotive TFT display module - Rashami Surendra Abhyankar (2016)
During the last decade, there has been a significant increased in the complexity of vehicular electronic design. One notable change is the use of thin film transistor (TFT) displays in the HMI panels. The trend is due to increased demand for more advanced graphical capabilities and lesser interest for electro-mechanical indicators. Electromagnetic compatibility (EMC) problem has become more challenging as the flexible printed circuit (FPC) cable behaves like an antenna, creating a lot of unnecessary emissions. For this project, the student is required to apply EMC simulation on an actual automotive cluster to display module through a commercial EM simulation tool. System level radiated emissions measurements will be carried on the actual product so as to evaluate the accuracy and limitation of the simulation tool. Once high confidence in the measurement and simulation results can be achieved, various counter-measures can be carried out through virtual prototyping.